2000
DOI: 10.1152/ajplung.2000.279.2.l371
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulation of vascular endothelial growth factor in human pulmonary epithelial cells

Abstract: Vascular endothelial growth factor (VEGF) is a potent endothelial cell growth and permeability factor highly expressed in rodent alveolar epithelium after injury and repair. To investigate VEGF synthesis in human lung epithelial cells, we examined VEGF expression by cultured cells under basal conditions and after cytokine treatment or oxidative stress. Basal VEGF expression was detected in transformed human epithelial cell lines (A549 and 1HAEo-) and in primary human bronchial epithelial cells with RT-PCR, Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
91
0
7

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(108 citation statements)
references
References 38 publications
8
91
0
7
Order By: Relevance
“…Similar findings have been reported in premature, non-human primates treated with oxygen and mechanical ventilation [32]. Transcripts corresponding to each of the major splice variants, VEGF 189 , VEGF 165 , and VEGF 121 , have been previously identified in A549 cells [33]. In the current study, exposure to hyperoxia failed to alter the expression of any isoforms over time or in comparison to cells grown in room air, demonstrating that alternate splicing cannot account for the increase in medium-derived VEGF.…”
Section: Discussionsupporting
confidence: 82%
“…Similar findings have been reported in premature, non-human primates treated with oxygen and mechanical ventilation [32]. Transcripts corresponding to each of the major splice variants, VEGF 189 , VEGF 165 , and VEGF 121 , have been previously identified in A549 cells [33]. In the current study, exposure to hyperoxia failed to alter the expression of any isoforms over time or in comparison to cells grown in room air, demonstrating that alternate splicing cannot account for the increase in medium-derived VEGF.…”
Section: Discussionsupporting
confidence: 82%
“…However, BOUSSAT et al [36] reported that primary human bronchial epithelial cells expressed VEGF and that the expression was upregulated by hypoxia and TGF-b1 treatment, as well as transformed human epithelial cells lines, including A549 cells [36]. The released VEGF from primary human bronchial epithelial cells was VEDF165 and had mitogenic activity of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the VEGF levels in the plasma, those in the epithelial lining fluid changed in the opposite direction with recovery from injury (37). Kaner et al (38) suggested that alveolar epithelial cells are damaged in ARDS, possibly leading to the decreased levels of VEGF, because alveolar epithelial cells are the predominant source of VEGF (39). Accordingly, increased VEGF levels in the alveolar space may reflect recovery from ARDS (37).…”
Section: Discussionmentioning
confidence: 99%